1999
DOI: 10.1176/ps.50.7.953
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From the First Two Years of Project Heartland, Oklahoma's Mental Health Response to the 1995 Bombing

Abstract: On April 19, 1995, a terrorist bombing in Oklahoma City killed 168 people and injured 853 others. The Oklahoma Department of Mental Health and Substance Abuse Services was the lead agency in crafting a community mental health response to reduce impairment of those affected. The Project Heartland program, which opened on May 15, 1995, was the first community mental health program in the U.S. designed to intervene in the short to medium term with survivors of a major terrorist event. The authors describe lessons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…20 Professional rescue and responder personnel are typically hesitant to use formal mental health services. The degree to which this extends to their partners and other family members awaits more comprehensive evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Professional rescue and responder personnel are typically hesitant to use formal mental health services. The degree to which this extends to their partners and other family members awaits more comprehensive evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducative modules were common and they were typically applied as a part of the CBT or creative intervention methods. For instance, the interventions studied by Call and Pfefferbaum [1999], Thabet et al [2005], and Vickers [2005] included information about children's common trauma responses, psychiatric symptoms and age-salient ways of understanding trauma. Narrative approach was either applied as the main technique of intervention [Onyut et al, 2005] or combined with other methods [Chase et al, 1999;Lustig et al, 2004].…”
Section: Techniques Tools and Underlying Mechanismsmentioning
confidence: 99%
“…It emphasizes crisis counseling and support services, along with outreach and public education for affected individuals. Consistent with this model, following the 1995 Oklahoma City bombing Project Heartland provided services to 9,345 individuals, most of whom were indirect community victims of the bombing (Call & Pfefferbaum, 1999). Subsequent evaluation has suggested that direct victims with more serious disorders may have been underserved in terms of screening, triage, referral to specialist services for established treatments, and subsequent monitoring.…”
mentioning
confidence: 99%